The construction of the intellectual field of the history of education and its contribution to Pedagogical Peace: An interdisciplinary perspective - Mora García, José Pascual (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In the present work, some of the results of the Postdoctoral Program (UPTC-Tunja) are preliminarily exposed, especially with regard to the construction of the intellectual field of the history of education and Pedagogical Peace (Marquardt et Al, 2019). Among the objectives, it seeks to analyze how this Intellectual Field was formed within the research groups Grupo Hisula-UPTC, Grupo Primo Levi de Justicia Social, Grupo Hedure (Universidad de Los Andes-Táchira, Venezuela), the Red Sociedad de Historia and Latin American Education (Shela), and the Comparative Constitutional CC Group (National University of Colombia). Methodologically, it is an interdisciplinary investigation, which takes up the guidelines of historiography,